Automated valuation model for livestock appraisal in loaning practice - Buzás, Ferenc; Kiss, Sándor (Applied Studies in Agribusiness and Commerce, 2014)
Actualization of loan security (mortgage) value is of major importance in Hungarian loaning practice. Due to the recession in economics, the value of agricultural portfolio of banks has decreased a great deal, though not to such a great extent as other branches of the economy. Depreciation of estate stock is compensated with additional collateral security. Besides other stock, often temporarily and out of necessity, livestock is presented as additional collateral security. From the loaners’ point of view, however, the registered inventory value does not guarantee security. The authors have set up an appraisal method giving professional guidance through automated valuation as to how dairy stock can be used as mortgage for loan security. Hereby we are to present the details of both the theory and the methodology of a model that is appropriate for the valuation of dairy livestock on an MS Excel basis. Thus, the process is fast and has more prospects for all parties in the loaning or leasing business. The method involves the features of livestock technology, the expected realized profit, and breed stock value. By the implementation of this method, the loaners can calculate the value of loan recovery (loan to value) with acceptable security.